Interventions for posttraumatic stress disorder: a review of the evidence base. (March 2017) - Kaminer, Debra; Eagle, Gillian T
Given high rates of trauma exposure in South Africa, mental health practitioners often need to deliver interventions to trauma survivors. While there have been few local trauma intervention studies, there is an extensive international evidence base that provides a rich resource on which to draw. This article reviews evidence-based treatments for posttraumatic stress disorder and complex posttraumatic stress disorder. The current weight of evidence supports the use of trauma-focused cognitive behavioural therapy approaches in the treatment of posttraumatic stress disorder and the use of multimodal, phase-based interventions to treat complex posttraumatic stress disorder. There is also a long-standing, though less extensive, evidence base for psychodynamic therapy in the treatment of these conditions, as well as a number of emerging treatment approaches that require further study. While there are some limitations to transferring these approaches to the South African context, the current evidence base provides valuable guidelines for local practitioners seeking to develop their competencies in treating posttraumatic stress disorder and more complex trauma-based presentations.